2019
DOI: 10.2298/vsp160831144j
|View full text |Cite
|
Sign up to set email alerts
|

Triple IgE-positivity to hornet, wasp and bee venom in the patient with anaphylaxis: Diagnostic and therapeutic approach

Abstract: Introduction. Triple-positivity (TP) or double-positivity (DP) for serum-specific immunoglobulin E (sIgE) antibodies against hornet venom (HV), wasp venom (WV) and/or honeybee venom (BV) causes significant problem in a selection of appropriate venom immunotherapy. However, DP/TP can be caused by cross-reactions resulting either from partial sequence identity of protein allergens in the venoms, or may be related to cross-reacting carbohydrate determinants (CCDs). Case report. A 60-year-old man was stung by a wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…2 Multiple-positivity could be avoided by measuring CCD-sIgE. 19,20 Our results showed that determination of sIgE to recombinant major allergens is especially useful for the patients, with multiple-positivity to venom extracts and those who could not identify the insect.…”
Section: Discussionmentioning
confidence: 86%
“…2 Multiple-positivity could be avoided by measuring CCD-sIgE. 19,20 Our results showed that determination of sIgE to recombinant major allergens is especially useful for the patients, with multiple-positivity to venom extracts and those who could not identify the insect.…”
Section: Discussionmentioning
confidence: 86%
“…28 However, skin-testing may show rVes v 5 should be based on CRD, severity of SAR and history of insect sting allergy. 27,30,31 Interestingly, the sensitivity of HBV-single-positivity was significantly increased after CCD-inhibition from 0% to 77% in our third group of HBV/WV/HV/CCD-positive honeybee allergic patients. In this group of patients CCD-inhibition can replace expensive CRD.…”
Section: Discussionmentioning
confidence: 54%
“…Although, Api m 2 shows a high percentage of homology with Ves v 2, 27,29 it can sometimes be difficult to determine whether these results reflect sensitization due to cross‐reactivity between the shared protein determinants or true double sensitization to both insect species. Since HBV‐allergic patients can have Api m 2 mono‐sensitization, a decision regarding VIT in patients with IgE‐reactivity to rApi m 2 and rVes v 5 should be based on CRD, severity of SAR and history of insect sting allergy 27,30,31 …”
Section: Discussionmentioning
confidence: 99%